PENGARUH CORPORATE SOCIAL RESPONSIBILITY DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PERUSAHAAN - Mu’Afi, Muhammad; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of Corporate Social Responsibility (CSR) disclosure and the firm size to the profitability of the company. This research applies explanatory research which has been done by using quantitative approach. The samples are 15 companies which have been selected by using purposive sampling method.The result of the research shows that CSR disclosure has positive influence to the profitability of the company whereas the firm size has negative influence to the profitability of the company.Keywords: Corporate Social Responsibility (CSR), Firm Size and Companyâs Profitability.